Potential promotion of activated carbon supported nano zero-valent iron on anaerobic digestion of waste activated sludge. Issue 23 (15th October 2022) - Zhou, Jun; Zhou, Ying; You, Xiaogang; Zhang, Haonan; Gong, Lei; Wang, Jin; Zuo, Tong
ABSTRACT: A large amount of waste activated sludge (WAS) harms the ecological environment, and anaerobic digestion (AD) is an effective method for WAS treatment. In this study, activated carbon (AC)/ nano zero-valent iron (NZVI) was synthesized by a liquid-phase reduction method, and was used to boost methane production. The associated mechanisms and effects of additives on AD during the addition and removal stage were investigated systematically. Compared to the blank group, the cumulative methane production was increased by 14.3%, 26.3% and 34.1% in the groups of AC, NZVI and AC/NZVI, respectively. The addition of AC/NZVI significantly increased the concentration of VFAs and promoted the hydrolysis and acidification of WAS. After the AD of the additives addition stage was finished, the additives were removed and the sludge was replenished in all groups, the methanogenesis performance of the experimental groups was significantly inhibited. The cumulative methane production in the AC and AC/NZVI groups was 21.7% and 13.5% lower than the blank group, respectively. The experimental results have a good correlation with curve fitting by the modified Gompertz model. The modified Gompertz model found that AC, NZVI and AC/NZVI increased the methanogenic potential and maximum methane production rate of WAS, but also prolonged the lag-phase time. AC/NZVI might play a role in coupling effects. It could not only maintain the original characteristics of NZVI and increase its stability, but also develop the advantages of AC promoting direct interspecies electron transfer. Microbial community analysis indicated that the abundance of hydrogenotrophic methanogens was enriched by AC/NZVI. GRAPHICAL ABSTRACT: UF0001